Descriptive anthropometry kelantanese recreational adolescent taekwondo practitioners - Fadzliana, Majid@ Jalil
The objective of this study was to describe the anthropometric profile of Kelantanese adolescent taekwondo practitioners and in specifically to compare the anthropometric profile between the males and females. Methods: Subjects were members of the taekwondo Kelantan state team training to participate in SUK.MA 2008 (8 males, 18.63±1.92 years, 168.65±7.37 em, 68.29±20.69 kg, and 10 females, 18.10±1.37 years, 158.22±4.11 em, 59.72±10.03 kg). Somatotype was assessed according to the Heath-Carter method (Carter and Heath, 1990), while the sum of 8 skinfolds (biceps, triceps, subscapula, supraspinale, iliac crest, abdominal, anterior thigh and medial calf) was used to represent relative total body fat. All measurements were taken following the ISAK. protocol. An independent t-test was used to determine the differences between males and females. The level of significance was set at 0.05. Results: The males were taller (p=0.002, eta2=0.476) but no difference in weight (p = 0.264, eta2 = 0.071). Although the females recorded a higher sum of 8 skinfolds (127.72 mm vs. 99.11 mm), this was not statistically significantly different (p=0.259, eta2=0.079). There was a difference in proportional weight between the males and females but no difference was found in proportional sum of skinfolds. There were also no differences in endomorphy (3.73 vs. 4.64, p=0.340, eta2=0.057), mesomorphy (5.45 vs. 4.86, p=0.431, eta2=0.039) or ectomorphy (2.34 vs. 1.44, p=0.254, eta2=0.081). Conclusion: This study concluded that the mean somatotype of the participants was endo-mesomorphic for both sexes. The females were more endomorphic than the males, while the males were more mesomorphic and ectomorphic from a practical point of view. It is not clear why there were no differences in somatotype between the males and females. It might be due to competition levels of these athletes or due to the weight divisions of the athletes